ANALYTICAL PROVISIONS OF INFLUENCE OF COMPLETENESS OF TECHNICAL CONTROL ON FAULTLESSNESS OF SELF-PROPELLED SPRAYERS - Lyubchenko, I. S.; Rogovskii, I. L. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2021)
The article discusses the impact of the parameters of built-in technical control, such as the completeness and depth of technical control, on the reliability of self-propelled sprayers. Analytical models of some typical failure-free structures of self-propelled sprayers have been developed, which take into ac-count the characteristics of technical control over the efficiency of the elements. A graphical interpretation of the dependence of the reliability of self-propelled sprayers on the completeness of technical control is presented. The existence of the influence of completeness of technical control on the indicators of failure of structures is confirmed. The considered approach with a similar analysis allows to reasonably make requirements to the characteristics of technical control systems of self-propelled sprayers.